Kualitas dan Daya Simpan Ikan Kakap Merah dengan Daun Kelor sebagai Pengawet Alami - Arizka, Novida Dwi; , Dra. Titik Suryani, M.Sc (2017)
Red snapper (Lutjanus sp.) is one of commodity fishery products which have high economic value. The red snapper contains water content of 79.31%, 16.30% protein, 0.05% fat and 0.23% carbohydrates. The red snapper rapid damage due to the activity of microorganisms that is need to be preservation. The content of Moringa leaf are tannins, steroids, triterpenoids, flavonoids, saponins, alkaloids antarquinon and so that can be used as a natural preservative to inhibit microbial activity. The purpose of this study was to determine the number of bacteria colonies, moisture content, pH, sensory test, the quality and shelf life of red snapper. The research method used a completely randomized design (CRD) with two factors, the first factor is the weight of Moringa leaf (R1=25g + 100ml aquades, R2=50g + 100ml aquades, R3=75g + 100ml aquades) and the sacond factor was soaking time (L1= 30', L2= 60') and control (-) was used aquades, control (+) 0,12 gram of sodium benzoat. The results showed the best quality red snapper in the treatment of R3L1 (75g Moringa leaf + 100ml aquades and a 30' soaking time) by the number of bacterial colonies 2,05x106 cfu / g, water content of 43.4% and a pH of 6. While the best storage in treatment of R3L1 (75g Moringa leaf + 100ml aquades and a 30' soaking time) with the appearance of red bright, fresh, meat texture rather soft, no fingerprints when pressed, gill color red-brown, stand out eyeballs, bright black pupils, shiny, clear corneal membranes and the shelf life of 18 hours they can be consumed.